A governança pelos números contra a linguagem da atividade - Antoine Duarte; Roxane Dejours (Universidade do Porto, 2020)
Starting from a research in psychodynamics of work, the paper aims to explain the consequences of the new forms of work organization on the activity of deliberation and cooperation of workers, on the one hand, and on their possibilities of development and action, on the other hand. It is particularly concerned with showing how the denial of reality and living labor, supported by managerial transformations in the organization of work, disqualifies the language of activity emanated from workers and bars access to effective work, thus "preventing" deliberation on living labor. Finally, it questions the necessary conditions for a reinstatement of deliberation, so that it takes precedence over a thought invaded by the social imaginary and that can open the way to the challenge of symbolic domination and to the resistance to governance by numbers.